Mechanical Behavior Of Cement Treated Sand With Ordinary Portland Cement (OPC) - Syirly A. W. Hariono; Bambang Piscesa; Wahyuniarsih Sutrisno; Laras L. Lestari (Institut Teknologi Sepuluh Nopember (ITS), 2025)
Cement Treated Sand (CTS) plays a pivotal role in enhancing poorly graded sandy soils, which inherently lack cohesion and pose challenges for infrastructure development. This study investigates the influence of varying cement percentages (6%, 8%, 10%, and 12% by dry weight of sand) on the mechanical properties of CTS. Tests were conducted for Unconfined Compression Strength (UCS) and California Bearing Ratio (CBR) to evaluate compressive strength and soil bearing capacity, respectively. The findings demonstrate that increasing cement content improves compressive strength but may diminish ductility. Therefore, optimizing cement ratios is essential to strike a balance between strength enhancement and material durability. This research underscores the critical role of CTS in stabilizing poorly graded sandy soils, offering valuable insights for enhancing infrastructure resilience in coastal areas prone to these soil types.